Bicarbonate toxicity to Ceriodaphnia dubia and the freshwater shrimp Paratya australiensis and its influence on zinc toxicity. (27th March 2014) - Vera, Carolina Lopez; Hyne, Ross V.; Patra, Ron; Ramasamy, Sunderam; Pablo, Fleur; Julli, Moreno; Kefford, Ben J.
Abstract Bicarbonate is often a major ionic constituent associated with produced waters from methane gas extraction and coal mining, yet few studies have determined its specific toxicity. Currently, the environmental risk of bicarbonate anion in water discharges is assessed based on the toxicity of sodium chloride or artificial seawater and is regulated via electrical conductivity. Increased NaHCO3 added to Ceriodaphnia dubia in synthetic or natural water gave similar 48‐h 10% effective concentration (EC10) values of 1750 ± 125 mg NaHCO3/L (mean ± standard error) and 1670 ± 180 mg NaHCO3/L, respectively. Bicarbonate was toxic to C. dubia in both waters with conductivities above 1900 µS/cm. In contrast, when conductivity was elevated with NaCl, toxicity to C. dubia was observed only above 2800 µS/cm. Bicarbonate also impaired C. dubia reproduction with an EC10 of 340 mg NaHCO3/L. Major ion composition also influenced Zn bioavailability, a common co‐occurring metal contaminant in coal mine waters, with sublethal concentrations of NaHCO3 and elevated pH increasing Zn toxicity. Higher pH was the dominant parameter determining a 10‐fold increase in the 48‐h 50% effective concentration (EC50) for Zn toxicity to C. dubia at pH 8.6 of 34 µg Zn/L (95% confidence limit = 32–37 µg Zn/L) compared with the Zn toxicity at approximately circumneutral pH. Exposure of the freshwater shrimp Paratya australiensis (Atyidae) in natural water to increasing bicarbonate gave a mean 10‐d 10% lethal concentration (LC10) of 850 ± 115 mg NaHCO3/L, associated with a mean conductivity EC10 of 1145 µS/cm, which is considerably lower than toxicity of NaCl and artificial seawater to this species reported elsewhere. Because toxicity was influenced by salt composition, specific ions should be regulated rather than conductivity alone in mine wastewater discharges. Environ Toxicol Chem 2014;33:1179–1186. © 2014 SETAC